A Novel Procedure of Prepuce Reconstruction Customized to the Religious Needs of Some Individuals - Gupta, Richie; Mehta, Sandeep; Gupta, Rajat (Indian Journal of Plastic Surgery, 2021)
Background Authors describe a novel procedure in a group of patients for prepuce reconstruction, ensuring complete glans penis coverage who had either been circumcised in childhood or had congenitally short prepuce.Methods Case records of all cases done by the novel method which involved penile degloving and maintenance of neoprepuce, with the help of de-epithelization of glans penis and a few key sutures performed over the period from January 2010 to December 2019 were reviewed retrospectively. A total of 46 patients, 32 had congenitally short prepuce and 14 had previous circumcision.Results All the patients had complete glans penis coverage. None of the patients had complications like urinary infection, meatal stenosis, collection in neoprepucial sac, balanitis, or posthitis. The mean followup was 23.24 months in 37 patients. Nine lost to followup.Conclusions The procedure is simple, gives reliable results, and is customized to the needs of the patients. It does not interfere with penile erections.
Keywords: prepuce reconstruction; circumcision; glans coverage; milah; periah